OPTIMIZING OF GROOVE ANGLE IN WELDING CAST ALUMINUM A356 FOR PRODUCT REPAIR - Wibowo, Heri; Marwanto, Arif; Putera, Raka Hilmi Syah; Fakhri, Ardani Ahsanul (Jurnal Dinamika Vokasional Teknik Mesin, 2025)
The purpose of this study was to investigate the effect of groove angle on the tensile strength, impact toughness, and hardness of A356 cast aluminum and to determine the most optimal groove angle for welding A356 cast aluminum. The research method used was a pure experiment by conducting tensile, impact, and hardness tests on welding specimens with groove angles of 0°, 30°, 55°, and 75°.  The test results showed that the 75o groove angle had advantages over other groove angles with a maximum stress of 26.396 N/mm2, a maximum strain of 10.341%, an elastic modulus of 1625.144 N/mm2, an impact toughness of 0.1518 J/mm2, and a Vickers hardness of 24.7 HVN. Based on the test results, it was concluded that the groove angle of 75o is the most optimal angle for welding A356 cast aluminum in the context of repairing cast aluminum products.